2016
DOI: 10.1177/1748895816641997
|View full text |Cite
|
Sign up to set email alerts
|

Payment by results: Challenges and conflicts for the Therapeutic Community

Abstract: Gosling, HJ Payment by Results. Challenges and Contradictions for the Therapeutic Communityhttp://researchonline.ljmu.ac.uk/3120/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LJMU Research Online to facilitate their private study or for non-commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…(Chandley and Rouski, 2014, p.87), and while it is recognised that adopting service user involvement principles is complex within secure environments, such principles have been found to be successfully adopted benefitting both service users and staff (McKeown et al, 2016b). However, consideration must be given when implementing therapeutic community principles within the modern healthcare landscape of payment-by-results directives (Gosling, 2016). Nonetheless, the power of supportive relationships which 'are undoubtedly integral features of mental health and well-being' (Middleton, 2017, p.264) should continue to be part of the debate as we move towards 'new meaning and purpose [as society] grows beyond the catastrophic effects of ' the global pandemic (Anthony, 1993, p.527).…”
Section: Discussionmentioning
confidence: 99%
“…(Chandley and Rouski, 2014, p.87), and while it is recognised that adopting service user involvement principles is complex within secure environments, such principles have been found to be successfully adopted benefitting both service users and staff (McKeown et al, 2016b). However, consideration must be given when implementing therapeutic community principles within the modern healthcare landscape of payment-by-results directives (Gosling, 2016). Nonetheless, the power of supportive relationships which 'are undoubtedly integral features of mental health and well-being' (Middleton, 2017, p.264) should continue to be part of the debate as we move towards 'new meaning and purpose [as society] grows beyond the catastrophic effects of ' the global pandemic (Anthony, 1993, p.527).…”
Section: Discussionmentioning
confidence: 99%
“…27 A pilot study of payment by results is currently evaluating incentives for delivery of recovery for drugs and alcohol in primary care. 28 If implemented, recording of drug misuse may improve. However, this could negatively impact the GP-patient relationship.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Analysing a PbR pilot scheme for 182,447 service users receiving treatment for drug dependency, Mason et al (2015: 1126) found that those ‘treated in pilot areas were significantly less likely to complete treatment’. Gosling (2016) states that PbR has commodified alcohol and drug treatment, diluting the values intrinsic to working with substance users due to the need to evidence results. Clist (2016: 290), moreover, argues that there is ‘very little related empirical evidence’ for PbR in the international development sector.…”
Section: Ticking Boxes: Pbr and ‘Penal Accountancy’mentioning
confidence: 99%
“…Robust measures of success can be difficult to discern, with PbR schemes exhibiting negligible differences with other international development projects (Clist, 2018). Accordingly, the evidence suggests that, under PbR, autonomy and innovation are ‘suffocated rather than promoted’ (Gosling, 2016: 529).…”
Section: Ticking Boxes: Pbr and ‘Penal Accountancy’mentioning
confidence: 99%